Enhanced Catalytic Activity of Iron‐Promoted Nickel on γ‐Al2O3 Nanosheets for Carbon Dioxide Methanation. Issue 6 (14th May 2018) - Mebrahtu, Chalachew; Abate, Salvatore; Chen, Shiming; Sierra Salazar, Andrés Felipe; Perathoner, Siglinda; Krebs, Florian; Palkovits, Regina; Centi, Gabriele
Abstract: Iron‐promoted nickel on γ‐Al2 O3 nanosheets shows enhanced catalytic activity, selectivity, and stability for carbon dioxide methanation, a relevant process for energy storage and transportation (power‐to‐gas) for the future low‐carbon economy. Nanosheet‐type catalysts were synthesized by a two‐step hydrothermal method and characterized by several physicochemical methods. The catalytic activity for CO2 methanation was investigated in the 300–350 °C temperature range at a pressure of 5 bar. A high activity at 300 °C (≈860 molCH4  molNi −1  h −1 ) and 99 % CH4 selectivity with a stable catalytic performance for more than 50 h were observed for the nanosheets‐based sample promoted with iron. With respect to a commercial methanation catalyst, the Fe‐promoted nanosheets‐based catalyst showed an integral rate of CO2 conversion to methane more than three times higher, with a rate of deactivation 5 times lower at 300 °C. With respect to nanosheets catalysts without the use of Fe as promoter, the rate of CO2 conversion is approximately 5 times higher, and with respect to a catalyst with the same composition, but prepared using a bulk‐type alumina, the activity is approximately 2.5 times higher. There is thus a synergistic role of the unique nanostructure and Fe promotion. The nanosheets structure promotes Ni dispersion, forming small Ni nanoparticles (≈11–13 nm) upon reduction, which are very stable with time on stream and against oxidation. Fe forms an alloy with Ni upon reduction and improves the dispersion and reduction degree. No relation is observed between the quantitative number of basic sites and turnover frequency (TOF) values, but data suggest that the mobility of adsorbed CO2 towards the Ni particles, favored by the weakening of medium‐strong basic sites related to Fe promotion and nanosheets structure, determines the reaction rate and TOF. Abstract : A much‐needed promotion : An Fe‐promoted Ni/Al2 O3 nanosheet‐like catalyst is synthesized using a two‐step hydrothermal method. Higher activity and excellent stability are obtained by the newly prepared material during catalytic CO2 methanation test.